Issues in International Taxation and the Role of the IMF. (Policy Papers; Policy Paper ;, 2013)
In the discussion of the Board work program on June 3, 2013, it was urged that the Fund be more present in current discussions of international tax issues. This note reviews key issues and initiatives in this area, and sets out a work plan that is focused on the Fund's mandate and macroeconomic expertise and that complements the work of other institutions, notably the OECD.